2019
DOI: 10.1186/s12955-018-1065-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the quality of life among Pakistani general population and their associated factors by using the World Health Organization’s quality of life instrument (WHOQOL-BREF): a population based cross-sectional study

Abstract: BackgroundMeasuring quality of life (QOL) in a population is important for the predictions of health and social care needs. In Pakistan, health related quality of life data exist but there are no quality of life data of general population. In this study, quality of life was assessed among the Pakistani general population and their associated factors by using the World Health Organization’s quality of life instrument (WHOQOL-BREF).MethodologyA population-based cross-sectional study was carried out in all 52 Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
4
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 35 publications
11
53
4
9
Order By: Relevance
“…Regular physical activity and exercise are associated with well-being, physical health, life satisfaction and improvement of conceptual functions [43] . In this context, quality of life involves the physiological integrity of individuals as well as psychological and social comfort [44] . In our study, the quality of life scores were lower in comparison to population-based cross-sectional studies conducted by similar methodologies [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regular physical activity and exercise are associated with well-being, physical health, life satisfaction and improvement of conceptual functions [43] . In this context, quality of life involves the physiological integrity of individuals as well as psychological and social comfort [44] . In our study, the quality of life scores were lower in comparison to population-based cross-sectional studies conducted by similar methodologies [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…27 They also scored higher in environmental domain when compared to Pakistani general population. 28 Several studies showed differences in the HRQOL scores by sex. Males usually had better scores than females.…”
Section: Discussionmentioning
confidence: 99%
“…A score ranging from 0, indicating the worst health status, to 100, indicating the best health status, is assigned for each domain [28]. The WHOQOL-BREF, a 26-item instrument, measures the following broad domains: physical health, psychological health, social relationships, and environment [29,30]. It contains 2 items on "overall QoL and general health and 24 items on satisfaction, which are evaluated in 4 domains: physical health, (7 items), psychological health (6 items), social relationships (3 items), and environmental health (8 items).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%